A Conceptual Analysis of the Knowledge of Prospective Mathematics Teachers about Degree and Radian - TUNA, Abdulkadir (Sciedu Press, 2013)
This study examined the knowledge levels of prospective mathematics teachers about the concepts of degree andradian, which are among the angle measuring units that constitute the basis of trigonometry, and the relationshipsbetween those concepts. The study group consisted of 93 prospective mathematics teachers attending a state universityin Turkey. Qualitative and quantitative research methods were used for data collection and analysis. 4 questions aboutthe concepts of degree and radian were asked to the prospective mathematics teachers. The responses of theprospective teachers were categorized as correct and incorrect. Then, incorrect answers were divided intosub-categories by means of coding method and presented in tables. According to research findings, 40% of theprospective mathematics teachers defined the concept of degree correctly while approximately 90% made an incorrectdefinition of radian.
Keywords: 4. Education